Ageism and Mistreatment of Older Workers 2012
DOI: 10.1007/978-94-007-5521-5_3
|View full text |Cite
|
Sign up to set email alerts
|

Harassment of Older Adults in the Workplace

Abstract: This chapter reviews research on harassment of older adults in the workplace and highlights results from my recent study of harassment of older workers in Maine. I suggest that the power that older people hold at work, at home, and in their communities shapes their workplace harassment experiences. Based on a survey of nearly 200 Maine workers aged 62 and above, four questions framed the study: (1) What is the contentof older workers' harassment experiences?; (2) Which older workers are most likely to become t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 64 publications
0
4
0
Order By: Relevance
“…Wainwright et al (2019) concluded that extending working life creates challenges in managing organizational change. Older workers are often harassed (Blackstone, 2013) creating conflict in the workplace.…”
Section: Organizational Complexitiesmentioning
confidence: 99%
“…Wainwright et al (2019) concluded that extending working life creates challenges in managing organizational change. Older workers are often harassed (Blackstone, 2013) creating conflict in the workplace.…”
Section: Organizational Complexitiesmentioning
confidence: 99%
“…In extreme circumstances, age-related harassment has also been observed. So is verbal offenses in front of other workers or consumers, age-related jokes, discrediting comments and behaviors, sexual offenses, and even physical aggression (Blackstone, 2013). Dismissals that penalize older workers are generally associated with negative age stereotypes.…”
Section: Rausp 552mentioning
confidence: 99%
“…The number of Age Discrimination in Employment Act (ADEA) complaints filed by those older than age 55 has steadily increased since 2000, during which their numbers have grown in the workplace [12,13]. Older workers report feeling that their contributions are unacknowledged, and they feel left out of decision-making and planning functions [14]. Ageist attitudes result in fewer work opportunities, training, promotions, and retention [15][16][17].…”
Section: Introductionmentioning
confidence: 99%